Destinos afines: Emile Cioran, Yasmina Reza y la apología de la impugnación - Villamía, Luis (Anales de Filología Francesa, 2020)
There is no doubt regarding the influence exercized by the work of Emile Cioran upon Yasmina Reza´s fictional texts. Not only some of her theater characters are inspired in the figure of Cioran, but both writers share a similar worldview and analogous obsessions that flourish in their writings. In this manner, we do perceive in them a kind of aggressiveness that turns against themselves seasoned with frivolity and humor. In the speeches and monologues of Reza´s characters we can identify ideas that are repeated endlessly in Cioran´s aphorisms. Both authors turn reflection into pleasure towards excess, as if they were unable to contain themselves. From this perspective, we can better understand ideas such as their rejection from the notion of happiness for being considered a desire vulgar and childish, and the apology for barbarism as the only way to be reborn again.